Energy Conservation Measures in Heavy Trucks Freight Transport - Tageldin Hago Ahmed, Suhail; Abdelrahman Rabah, Ali (Journal of Energy Conservation, 2020)
Since the independence of South Sudan, Sudan lost 75% of its oil reserves, this led to major fuel shortages country wide, the fuel shortage raised the fuel prices and the overall transport prices. Scarcity led to black market trade of fuel specially in states away from the Capital City (Khartoum). Managing the available stock comes first before increasing the supply amount in order to solve the problem, one of the major fuel consumers to be managed is the transport sector specially the long haulage freight transport. Moving freight in Sudan is constrained by inadequate infrastructure and high costs. This paper covers specifically the long haulage freight transport between Khartoum State and Western side of the country (Darfur Region), Contributing to manage fuel consumption for trucks, taking into account trucks types used, roads, environmental impacts and mitigation measures applicable to save fuel . The results showed that the primary reason for the excessive fuel consumption is the usage of the rigid trucks (lorries) for transport specially the Hino700 series, this truck type, overload and absence of weight stations and control policies contributed significantly to deterioration of roads and transport efficiency decreasing. First step towards the solution would be in upgrading roads infrastructure assuring high quality along with enforced weight regulations and weight stations to protect roads from damages. High quality roads shall ease the usage of different truck types with different configurations. Then stablish a policy to force replacement of the low efficiency lorry truck types with high quality tractor semi-trailer combinations.
Keywords: Sudan Energy Shortage; Global Warming; Environmental Impact; Trucks Types; Fuel Consumption.